Mitochondrial Quality Control in Alzheimer’s Disease: Insights from Caenorhabditis elegans Models - Upasana Ganguly; Trae Carroll; Keith Nehrke; Gail V. W. Johnson (Antioxidants)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder that is classically defined by the extracellular deposition of senile plaques rich in amyloid-beta (Aβ) protein and the intracellular accumulation of neurofibrillary tangles (NFTs) that are rich in aberrantly modified tau protein. In addition to aggregative and proteostatic abnormalities, neurons affected by AD also frequently possess dysfunctional mitochondria and disrupted mitochondrial maintenance, such as the inability to eliminate damaged mitochondria via mitophagy. Decades have been spent interrogating the etiopathogenesis of AD, and contributions from model organism research have aided in developing a more fundamental understanding of molecular dysfunction caused by Aβ and toxic tau aggregates. The soil nematode C. elegans is a genetic model organism that has been widely used for interrogating neurodegenerative mechanisms including AD. In this review, we discuss the advantages and limitations of the many C. elegans AD models, with a special focus and discussion on how mitochondrial quality control pathways (namely mitophagy) may contribute to AD development. We also summarize evidence on how targeting mitophagy has been therapeutically beneficial in AD. Lastly, we delineate possible mechanisms that can work alone or in concert to ultimately lead to mitophagy impairment in neurons and may contribute to AD etiopathology.